2013
DOI: 10.1111/cas.12210
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and esophageal squamous cell carcinoma risk in Kashmir, India

Abstract: Studies have persistently associated esophageal squamous cell carcinoma (ESCC) risk with low socioeconomic status (SES), but this association is unexplored in Kashmir, an area with a high incidence of ESCC in the northernmost part of India. We carried out a case-control study to assess the association of multiple indicators of SES and ESCC risk in the Kashmir valley. A total number of 703 histologically confirmed ESCC cases and 1664 controls matched to the cases for age, sex, and district of residence were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
81
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 42 publications
12
81
0
Order By: Relevance
“…Similar finding was observed in Pakistan (Moore et al, 2010a). On the other hand, inverse association between EC incidence rate and SR in the current study is in line with previous individual and ecological studies (Brown et al, 2001;Singh et al, 2002;Weiderpass and Pukkala, 2006;TorresCintron et al, 2012;Jansson et al, 2005;Dar et al, 2013;Ljung et al, 2013). It is argued that risk factors of EC such as smoking, low consumption of fruit and vegetables and obesity are more prevalent among people and areas with low SR (Ellaway et al, 1997;Dubowitz et al, 2008;Hiscock et al, 2012;Di Cesare et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar finding was observed in Pakistan (Moore et al, 2010a). On the other hand, inverse association between EC incidence rate and SR in the current study is in line with previous individual and ecological studies (Brown et al, 2001;Singh et al, 2002;Weiderpass and Pukkala, 2006;TorresCintron et al, 2012;Jansson et al, 2005;Dar et al, 2013;Ljung et al, 2013). It is argued that risk factors of EC such as smoking, low consumption of fruit and vegetables and obesity are more prevalent among people and areas with low SR (Ellaway et al, 1997;Dubowitz et al, 2008;Hiscock et al, 2012;Di Cesare et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…In case of EC, studies reported an inverse association between incidence and mortality rates and SR of individuals and regions (Brown et al, 2001;Weiderpass and Pukkala 2006;Torres-Cintron et al, 2012;Dar et al, 2013;Ljung et al, 2013). In Iran, a previous study conducted in Golestan province with high risk of EC showed an inverse relation between EC incidence and SR (Islami et al, 2009).…”
Section: Gender and Social Disparities In Esophagus Cancermentioning
confidence: 99%
“…The previous studies (Wang et al, 2007;Zhang et al, 2012;Dar et al, 2013;Hakami et al, 2013) have suggested that living in rural area is a risk factor for ESCC, as there are worse socioeconomic level, and more unhealthy eating habits. However, the exact statistical difference in prevalence of ESCC between urban and rural areas are not mentioned in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Income was an important factor, and those individuals with a low income (<$10,000 per year compared with those earning $25,000 or more annually) had a substantially increased risk of developing ESCC (African American OR: 8.00, 95 % CI: 4.30-15.00; Caucasian OR: 4.30, 95 % CI: 2.10-8.70). Another case-control study from India compared 703 cases of ESCC with 1664 controls matched by age, sex, and geographic area [ 45 ]. After adjusting for ethnicity, place of residence, religion, education, fruit intake, vegetable intake, smoking status, hookah, nass and ever use of bidi, gutka, and alcohol consumption, there was a strong relationship between occupations requiring physical activity and ESCC (OR: 5.65, 95 % CI: 3.49-9.12).…”
Section: Socioeconomic Statusmentioning
confidence: 99%